PENGEMBANGAN GAME PEMBELAJARAN MATEMATIKA BERBASIS ANDROID MENGGUNAKAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMPN 13 MERANGIN - Ana Mulisoh; Muhammad Jainuri; Hidayati Rais (Hiradika | Hira Institute, 2026)
Less active learning activities, low learning motivation, and the learning outcomes in mathematics of the students at SMP N 13 Merangin are the driving forces behind this study. The goal of this project is to use the Quizizz app to create an Android-based learning game with useful, practical, and efficient features. This study employs the ADDIE development model in conjunction with the Research and Development (R&D) method. Five validators—material experts, linguists, media experts, and practitioners—performed the validity test. The Android-based math learning game's validation results show a very valid category with an average overall validation score of 4.69. Practicality is assessed by a practicality questionnaire, an average score of 4.38% with a practical category, the results of the interview also show the practical category. Product effectiveness is obtained from learning activities with a percentage of 75.44% with an effective category, learning outcomes are obtained on average with a percentage of 83.00% with an effective category, and learning motivation is obtained with a percentage of 81.25% indicating an effective category. This demonstrates that this media is engaging, easy to use, and helps students learn more actively, improving learning outcomes and increasing motivation. Based on the research above, it can be concluded that the Android-based learning game developed using the Quizizz application is highly valid, practical, and effective. Furthermore, this learning game can be an alternative digital-based teaching material for educators in mathematics learning.